(3GdWQGR GdehTi aj GdEfTGs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
(3fSNI cJGH hQO Ydi GdCHhGH GdTQjaI GdedcjI GdXGgQjI NTbOe ef GdTjN HQgGf GdOjf GdHGYhfj GdTGaYj hjOje EeOGOg HGdYfGjI GdUeOjI hjMhVg HhbGjfI GdSQeOjI s
(3BNQgG (B:s
(3hEf de JHJg eOOfG Edjg jOkG aCNPfGg CNPkG hHjdkG aJbYO ePehekG eOMhQkG, Ef gPg JPcQI aef TGA GJNP Edi QHg SHjdG Je GdWQGR GdehTi aj GdEfTG s
(3GdfSNI HgG MhGTs
(3ChdgG JedjcGJ CbOegG (B1084(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B21 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs